Effect of Carrier Types and Spray Drying Temperature on The Physicochemical Properties of Turmeric Coffee - Hafizal, Rabiatul Adawiyah; Mohd Kassim, Angzzas Sari; Razali, Nor Faizah (Progress in Engineering Application and Technology, 2022)
Instant coffee has many issues regarding its ingredients and the amount of sugar contained in one sachet of 3 in 1 coffee. Nowadays, people have raised their awareness in practicing a healthy lifestyle thus by producing a healthier coffee mixture such as turmeric-coffee can be an alternative to promote a healthierlifestyle. On another hand, in producing turmeric coffee granules, the spray drying process would require a suitable operating condition to avoid problem such as stickiness of product material to the equipment glass and hence resulting in lower yield. This project aims to develop a healthier turmeric coffee-based granule with a suitable spray drying inlet temperature and its carrier as well as identifying the nutritional components such as total phenolic compound and total antioxidant activity. The bioactive ingredients of turmeric were extracted by using the subcritical water extraction method (SWE). The temperatures of 190 ˚C, 200 ˚C and 210 ˚C were chosen to determine the suitable inlet temperature of the spray drying process based on its physicochemical properties. For the best carrier and concentration, maltodextrin and Arabic gum at the concentration of 1%, 3% and 6% were used were. The total phenolic content and antioxidant activity were determined using Folin-ciocalteu method and DPPH assay respectively. The study has successfully determined the best inlet temperature at 190 ˚C with 5% Arabic gum as the optimum carrier for the highest yield (2.85%) and solubility (94.7%) contents and the lowest moisture content (4.17%). When using maltodextrin as the carrier, both the TPC (18.67 GAE mg/mg) and the TAA (72.89%) contents of the turmeric coffee granules were increased, probably due to the heat treatment from spray drying process. Meanwhile, the TAA decreased (44.66%) when Arabic gum was used as the carrier. The findings of this study will shed the understanding upon the production of an alternative instant coffee as a healthy drink for the long term.